The effect of inter-incisor opening, cavity location, and operator experience on the energy delivered by light curing unit to simulated dental restoration - Santini, Ario; Roebuck, Elizabeth; Harun, Nor Asilah (Wiley Blackwell, 2013)
Background Curing of resin composites depends on delivery of adequate total-energy, which may be operator dependent. Aim To determine the effect of inter-incisal opening, cavity location and operator experience on the total-energy delivered to simulated preparations. Design The following were recruited: junior dental nurses(5), senior dental nurses(5) and qualified dentists(5). Each operators light cured two simulated restorations in MARC™patient-simulator using a Demi™LCU, for 20 seconds and the total-energy was calculated: (1) tooth 27, Class 1 cavity, inter-incisal opening 25mm and 45mm; (2) tooth 11, Class III cavity. The procedure was repeated 5 times for each simulated cavity. Statistically comparisons (Kruskal-Wallis Test: alpha=0.05) of the following were made: between inter-incisal openings; between location and between the three groups in the total-energy delivered (J/cm² (Mean±SD)). Results Less total-energy was delivered to posterior cavity at 25mm (12.13±5.27 J/cm²) versus at 45mm (16.92±5.64 J/cm²) by all operators (p<0.05). At 45mm, less total-energy delivered to the posterior cavity compared to anterior cavity (25.07±7.35 J/cm²) and it was statically significant (p<0.05). There was no statistically difference between junior nurses and qualified dentists (p>0.05) but there was significant difference in the total-energy delivered between senior nurses (20.07±7.79 J/cm²) and junior nurses (17.49±7.57 J/cm²) and, between senior nurses and qualified dentists (16.55±8.70 J/cm²) (p<0.05). Conclusions Inter-incisal mouth opening, location of the cavity, and operators experience in light curing, affected the total-energy delivered to cavities in a simulated clinical environment.